2011
DOI: 10.1016/j.stem.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

CD24+ Liver Tumor-Initiating Cells Drive Self-Renewal and Tumor Initiation through STAT3-Mediated NANOG Regulation

Abstract: Tumor-initiating cells (T-ICs) are a subpopulation of chemoresistant tumor cells that have been shown to cause tumor recurrence upon chemotherapy. Identification of T-ICs and their related pathways are therefore priorities for the development of new therapeutic paradigms. We established chemoresistant hepatocellular carcinoma (HCC) xenograft tumors in immunocompromised mice in which an enriched T-IC population was capable of tumor initiation and self-renewal. With this model, we found CD24 to be upregulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
446
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(468 citation statements)
references
References 51 publications
18
446
2
2
Order By: Relevance
“…CSCs, also called tumor-initiating cells or cancer stem-like cells, possess stem cell features in their self-renewal and differentiation capacity, and contribute to the formation of heterogeneous tumor cell populations. In HCC, several stem cell markers, including CD133, CD90, CD13, epithelial cell adhesion molecule (EpCAM), and CD24, have been reported to enrich side populations of CSCs [13][14][15]. We recently reported that the stem cell markers EpCAM and alpha-fetoprotein (AFP) can be used to classify HCC subtypes with distinct gene expression profiles and patient prognoses [11].…”
Section: Introductionmentioning
confidence: 99%
“…CSCs, also called tumor-initiating cells or cancer stem-like cells, possess stem cell features in their self-renewal and differentiation capacity, and contribute to the formation of heterogeneous tumor cell populations. In HCC, several stem cell markers, including CD133, CD90, CD13, epithelial cell adhesion molecule (EpCAM), and CD24, have been reported to enrich side populations of CSCs [13][14][15]. We recently reported that the stem cell markers EpCAM and alpha-fetoprotein (AFP) can be used to classify HCC subtypes with distinct gene expression profiles and patient prognoses [11].…”
Section: Introductionmentioning
confidence: 99%
“…These cells are able to self-renew and differentiate into the bulk tumor population (10). Being a built-in population of tumor, these T-ICs can survive chemotherapy and repopulate the tumor (11). Accumulating evidence has showed that T-ICs exist in various tumors, including leukemia (12), glioma (13), breast (14), and colon cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has showed that T-ICs exist in various tumors, including leukemia (12), glioma (13), breast (14), and colon cancer (15). Liver T-ICs have also been identified by several cell surface antigens such as CD133 (16), CD90 (17), CD24 (11), and epithelial cell adhesion molecule (18). Existence of T-ICs in hepatocellular carcinoma is likely to be one of the most principle reasons why current oncologic therapies exhibit poor effectiveness (10,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Common chemotherapies have been shown to enrich the CSC subpopulations in some studies (4,34). CD133 þ hepatocellular carcinoma CSCs may confer chemoresistance by preferentially expressing the Akt/Bcl-2 or PTEN/Akt/ABCG2 pathway (13,30).…”
Section: Discussionmentioning
confidence: 99%
“…CSCs appear to be protected from routine chemotherapeutic drugs through various mechanisms, such as high expression levels of ATP-binding cassette (ABC) drug transporters (3). Drug-resistant CSCs have been shown to survive treatment with several widely used chemotherapeutic agents (4,5).…”
Section: Introductionmentioning
confidence: 99%